The Dynamics of Internal Communication Co-Orientation in Family Business Startups: A Case Study of Intergenerational Communication at the Padel Side - Zahra Shafwah Alaydrus; Azwar Azwar (Green Publisher Indonesia, 2025)
This study analyzes the internal communication co-orientation dynamics at a family business startup, The Padel Side, amidst the generational gap between Millennial management and Gen Z staff. Using an explanatory qualitative case study method (Yin, 2018) and Organizational Co-orientation Theory (Taylor, 1993), the research identifies four fundamental distortions: (1) a false consensus effect at the management level that creates a decision-making